Effect of Plant Extracts, Bio-insecticides, Petroleum Oil and Insecticides for Controlling Rose beetle (Adoretus compressus, Coleoptera: Scarabaeidae: Rutelinae) in Immature Oil Palm - Thongjua, T.; Thongjua, J. (International Journal of Agricultural Technology, 2018)
The adult of rose beetles feed on the leaves of oil palm (Elaeis guineensis jacq.) that cause to be decreasing of growth rate. The outbreak of these beetles is usually found in new planting area. It is necessary for farmers to use insecticides for controlling. The effect of pesticides to control rose beetle in 2-year-old oil palm plantation was conducted in Thungsong district, Nakhon Si Thammarat province, Thailand from July, 2015 to January, 2016. Result showed that the effectiveness of treatment after the last spraying was carbaryl 85% WP followed by carbosulfan 20% EC, petroleum oil 83.9% EC, bactospeine FC, tobacco 3%, Thai neem extract (azadirachtin 0.05%), which were 85.93 80.71 79.97 63.86 60.00 and 56.37%, respectively, compared with non-treated control. The integrated pest management (IPM) program to control rose beetle was resulted after treated with M1 (tobacco 3%), M2 (petroleum oil 83.9% EC 40 ml/20 L.of water), M3 (carbaryl 85% WP 60 g./20L.of water, M4 (tobacco 3% (3%)+ carbosulfan 5% G 200 g./tree), M5 (petroleum oil 83.9% EC 40 ml/20L. of water+carbosulfan 5% G 200 g./tree), M6 (carbaryl 85% WP 60 g./20L. of water+carbosulfan 5% G 200 g./tree), M7 (carbosulfan 5% G 200 g./tree and M8 (non-treated control). The highest effectiveness methods were M6 (100%), followed by M3, M7, M4, M5, M2 and M1 which were affected to control as at 86.62 74.98 73.86 70.59 66.54 and 62.82 %, respectively, which compared to M8.